TASK-BASED LANGUAGE TEACHING: ADVANTAGES AND CHALLENGES IN EFL CLASSROOMS. - Bozorboeva Lobar Alisher qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Task-Based Language Teaching (TBLT) has garnered widespread attention in the context of English as a Foreign Language (EFL) instruction because of its learner-centered orientation and communicative authenticity. This article explores both the advantages and the challenges of implementing TBLT in EFL classrooms, drawing on empirical studies and theoretical discussions. It examines how TBLT fosters communicative competence, learner motivation, and contextualized language use, while also considering constraints such as teacher preparedness, assessment alignment, classroom management, and cultural expectations. Implications for practice and future research directions are presented.